Fatigue loading characteristic for the composite steel-concrete beams - Ahmed I.Hassanin; Hesham M. Fawzy; Ahmed I. Elsheikh (Fracture and Structural Integrity)
During the past few decades, composite beams (steel I beam and concrete slab) have had a wide range of uses, particularly in bridge construction. This is due to its relatively low economic cost compared to individual steel structures or reinforced concrete structures. This type of bridges in particular and many similar industrial structures in general are repeatedly subjected to fatigue loads, and that is frequently, as a result of the vehicles passing on these bridges or the vibrations caused by the machines in the industrial facilities. It has been observed during the successive studies that they have been interested in studying this problem that it is concerned with the external structural behavior of these beams  such as a load –deflection relation, observing the cracks appearing during the failure stage and the strain in the steel and concrete flanges. Hence, in this study we have focused on several factors affecting mode of failure of these beams under the fatigue loads, and the common element in all stages of failure was the shear stud, specifically the welding collar at the base of this stud as it is a structurally weak region.